Status of the coral reefs in Foul and Folly Bays, Morant Wetlands, south-eastern Jamaica, with emphasis on corals and macroalgae - Chin, Denise A. (2014)
Foul and Folly Bays are located within the Morant Wetlands near the eastern tip of Jamaica. They have never been investigated but were believed to be important for larval productivity because of the extent of benthic habitats, absence of major coastal developments and remote location. The study was aimed at providing baseline data on the spatial distribution and status of corals and associated benthos. We investigated coral reefs and associated areas with phototransects at eight stations analysed with the Coral Point Count software. Most areas were dominated by algae, evidence of a phase shift from coral to algal reefs. Coral cover varied significantly across the bays (ANOVA, p= 0.0342) with a maximum of 27.03% at the deepest station and a mean of 5.6% at all other stations combined. Mean cover of macroalgae was 39% and varied significantly across stations (α= 0.05, F= 7.472, p= 0.005). The deepest station also had the highest percentage of calcareous algae and live coral while dead coral with algae (DCA) was a significant variable across all other stations (ANOVA, p<0.001). Gorgonians (ANOVA, p<0.001), sponges and urchins were also assessed. Diadema antillarum was not observed at any station. Overall the status of the reefs was poor, probably due to overfishing, absence of urchins and the resultant algal proliferation. Rev. Biol. Trop. 62 (Suppl. 3): 39-47. Epub 2014 September 01.